VAP code: A secure graphical password for smart devices. (April 2017) - Azad, Saiful; Rahman, Musfiq; Ranak, M. S. A. Noman; Ruhee, B. M. F. Kamal; Nisa, N. Nourin; Kabir, Nazrul; Rahman, Arafatur; Mohamad Zain, Jasni
Highlights: A new graphical password scheme is proposed, which is capable of tackling three prominent attacks, namely shoulder surfing, smudge attack, and brute force attack. In the proposed technique, the typical vibration mechanism of smart devices is transformed into a code, called Vibration Code (VC). To increase the password space of the proposed scheme, the VC is blended with a modified Pattern Lock (PL) system so that no extra effort is necessary. Graphical abstract: Abstract: In parallel to the increasing purchase rate of the smart devices, attacks on these devices are also increasing in an alarming rate. To prevent these attacks, many password-based authentication schemes are proposed. Among them, graphical password schemes are preferred on these devices due to their limited screen size and a lack of full sized keyboard. Again, existing graphical password schemes are susceptible to various attacks, among which shoulder surfing, smudge attack, and brute force attack are the most prominent. Hence, in this paper, we propose Vibration-And-Pattern (VAP) code, a new graphical password scheme that is resilient against these three major attacks. To evaluate the usability of our proposed scheme, a usability study has been conducted on 122 participants of various age groups from different demographics.